2005
DOI: 10.1038/sj.mp.4001739
|View full text |Cite
|
Sign up to set email alerts
|

Genetic investigation of chromosome 5q GABAA receptor subunit genes in schizophrenia

Abstract: We previously performed a genome-wide linkage scan in Portuguese schizophrenia families that identified a risk locus on chromosome 5q31-q35. This finding was supported by metaanalysis of 20 other schizophrenia genome-wide scans that identified 5q23.2-q34 as the second most compelling susceptibility locus in the genome. In the present report, we took a two-stage candidate gene association approach to investigate a group of gamma-aminobutyric acid (GABA) A receptor subunit genes (GABRA1, GABRA6, GABRB2, GABRG2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 105 publications
3
88
0
1
Order By: Relevance
“…Consistent with this interpretation, a recent genetic study reported that variants in the GABA A receptor a1 subunit gene were associated with both schizophrenia and altered expression levels of GABA A receptor subunit mRNAs. 66 Furthermore, a targeted deletion of the GABA A receptor a1 subunit gene in mice resulted in altered cortical expression of other GABA A receptor subunits, such as increased a2 and decreased g2 protein levels, as well as decreased levels of SST mRNA. 67,68 Together, these findings suggest that the deficit in a1 subunit expression could be an upstream event to other GABA-related gene expression changes in the DLPFC of subjects with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this interpretation, a recent genetic study reported that variants in the GABA A receptor a1 subunit gene were associated with both schizophrenia and altered expression levels of GABA A receptor subunit mRNAs. 66 Furthermore, a targeted deletion of the GABA A receptor a1 subunit gene in mice resulted in altered cortical expression of other GABA A receptor subunits, such as increased a2 and decreased g2 protein levels, as well as decreased levels of SST mRNA. 67,68 Together, these findings suggest that the deficit in a1 subunit expression could be an upstream event to other GABA-related gene expression changes in the DLPFC of subjects with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…17). Genome-wide linkage scans of Portuguese families identified a genomic region that includes GABRA1 (55), and haplotypes and SNPs in the gene are also associated with risk for SCZ, as well as alterations in the expression of GABAR subunits (56). Moreover, GABAR α1 transcript levels are lower in the postmortem brain of persons diagnosed with SCZ (19) and depression (57), suggesting a functional role of GABAR α1-containing receptors in the etiology of these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…39 One of the most attractive candidate regions for schizophrenia on 5q31-35 that maps several GABA(A) receptor subunit genes, recently gained positive results for an association with the disorder. 40 However, further investigations are warranted considering that a concurrent study in a Japanese schizophrenic population failed to confirm this. 41 Further interest in schizophrenia susceptibility on this chromosome has been stirred by a case report of a segmental uniparental isodisomy on 5q32-qter (the offspring receives two chromosomal homologs from one parent) in a patient with childhood-onset schizophrenia.…”
Section: Chromosomementioning
confidence: 98%